Pro Angular : build powerful and dynamic web apps - Freeman, Adam, 1972- (Apress, 2022)
Welcome to this one-stop shop for learning Angular. Pro Angular is the most concise and comprehensive guide available, giving you the knowledge you need to take full advantage of this popular framework for building your own dynamic JavaScript applications. Angular is an open-source JavaScript library maintained by Google. It has many excellent options when it comes to server-side development and is used in some of the largest and most complex web applications in the world to enhance HTML in the browser. Its cornerstone is the ability to create applications that are extendable, maintainable, testable, and standardized. Knowing Angular's foundations and understanding its applications is an asset in any developer toolbox. The fifth edition of this popular guide explains how to get the most from Angular, presenting the range of benefits it can offer. You will begin learning how to use Angular in your projects, starting with the nuts-and-bolts concepts, and progressing to more advanced and sophisticated features. Each topic in this full-color book provides you with precisely enough learning and detail to be effective. In true Adam Freeman style, the most important features are given full-court press treatment, while also addressing common problems and how to avoid them.